Prevalence of micronutrient deficiency and its impact on the outcome of childhood cancer: A prospective cohort study. Issue 7 (July 2022) - Ganguly, Shuvadeep; Srivastava, Richa; Agarwala, Sandeep; Dwivedi, Supriya; Bansal, Priyanka Gupta; Gonmei, Zaozianlungliu; Toteja, Gurdayal Singh; Dhawan, Deepa; Bakhshi, Sameer
Summary: Background & aims: Impact of micronutrient deficiency on childhood malignancy is unexplored. We estimated the prevalence of baseline micronutrient deficiency in children with cancer and its impact on event-free survival (EFS) and overall survival (OS). Methods: A longitudinal cohort study was conducted at a tertiary cancer centre in India. Children (≤18 years) with de novo malignancy were enrolled between October 2012 and May 2014. Baseline levels of vitamin B12, folate, zinc, selenium, copper, and iron were measured and values below 150 pmol/L, 6 ng/mL, International Zinc Nutrition Collaborative Group cut-off, 0.5 μmol/L, 10 μmol/L, and 50 μg/dL, respectively, indicated deficiency. Results: Total 535 children [326 (60.9%) haematological and 209 (39.1%) solid malignancies] were enrolled with median follow-up of 66 months. Vitamin B12, folate, zinc, selenium, copper and iron deficiencies were found in 209 (39.1%), 89 (16.6%), 173 (32.3%), 39 (7.3%), 12 (2.2%), and 231 (43.2%) children, respectively. Selenium deficiency independently predicted poor EFS (hazard ratio [HR] = 1.56; p  = 0.038) and OS (HR = 1.65; p  = 0.027) in the cohort. In haematological malignancies, selenium deficiency predicted poor EFS (HR = 1.81; p  = 0.023) and OS (HR = 2.12; p  = 0.004). In solid malignancies, vitamin B12 (HR = 1.55; p  = 0.028) and zinc (HR = 1.74; p  = 0.009) deficiencies predicted poor EFS, and zinc deficiency predicted poor OS (HR = 1.77; p  = 0.009). Multiple micronutrient (≥3) deficiencies also predicted poor EFS (HR = 1.69; p  = 0.001) and OS (HR = 1.83; p  < 0.001) in the whole cohort. Conclusions: Selenium deficiency was independently predictive of adverse outcomes in childhood cancer, particularly in haematological malignancies. Zinc deficiency adversely affected solid tumours. The adjunct use of micronutrient supplementation in paediatric malignancies should be explored.